Influence of membrane structure-dependent water transport on conductivity-permselectivity trade-off and salt/water selectivity in electrodialysis: implications for osmotic electrodialysis using porous ion exchange membranes - Liu, Hong (2022)
Water transport, including osmosis and electroosmosis, is an important phenomenon in electrodialysis (ED) but is generally ignored in many studies on the analysis of ion transport. Having a fundamental understanding of the influence of water transport on ion transport during ED is of particular help for the optimization of the design of ion exchange membranes (IEMs) and the development of novel ED-related processes. In this study we systematically investigated the effect of membrane structure-dependent water transport on ED performance and explored the potential of using porous IEMs in ED. A 1-D model, which is based on the extended Nernst–Planck equation and duly considers the membrane structure-dependent water flux, was developed to analyze mass (ion and water) transport in IEMs during ED. Results show that the electroosmotic flux increased with increasing the water volume fraction and the pore size of IEMs and decreasing the thickness of IEMs, which further leads to the increase in counterion flux and the decrease in co-ion flux. Osmotic water flux exhibited a similar trend to electroosmotic flux with changing membrane structural properties. The existence of osmotic water transport further enhanced the change of counterion and co-ion fluxes, which leads to the increase in both membrane conductivity and permselectivity. This suggests that osmotic water transport can break the trade-off between conductivity and permselectivity of IEMs during ED. On the other hand, osmotic water transport leads to the decrease in specific salt flux (i.e., the ratio of salt flux over water flux) despite the increase in salt flux, suggesting the decrease in salt/water selectivity. The effect of osmotic water transport is more significant for porous IEMs due to higher osmotic water flux compared to dense IEMs. This work provides new insights into the use of porous IEMs in osmotic electrodialysis for potential applications.